Challenges and constraints in meeting international standards in UAE education: External objectives versus local realities - Kathy O'Sullivan (13323315) (2015)
The purpose of this paper is to examine some of the challenges faced by a private university in the United Arab Emirates in balancing the specific needs of the country's educational system with the requirements of both national reporting measures and international accreditation. It highlights some critical issues, restraints and innovations in education reform. A higher education system of quality is necessary for the evolution of a society. Yet, in an increasingly globalised world, when information regarding local culture and the local community is subsumed by standardised information required by international accreditation agencies, higher education institutions are tasked with matching the ambitious goals they have with very diverse local realities. In-depth interviews with administrators, faculty members and students resulted in narratives that shed light on what participants perceive as the challenges to achieving international standards in an environment with many local constraints. Strategic questions are also posed as to what shape the development of a national higher education system should take. This is against the backdrop of a recent proliferation of branch campuses of foreign universities and private universities in the Gulf region in general, and the United Arab Emirates in particular, that are primarily self-funding. This study provides recommendations to educational leaders and policy planners to arrive at plausible, meaningful solutions to the issue of taking into account often-neglected local contextual realities, to help provide for quality education to the local population while at the same time meeting international standards. Other Information Published in: Near and Middle Eastern Journal of Research in Education, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/nmejre.2015.4